Study of the Demand for University Careers at the Baccalaureate Level - Aguilar Rodríguez, Iliana (2016)
The present research is directed to show the importance of higher education for high school students in the public, fiscal, fiscomisionales and municipal institutions from the Quito Canton, Pichincha province, allowing the analysis of several variables such as: university positioning, diverse options of faculties and careers, study schedules and training camps. It is necessary for the Instittutions of Higher Education (IES) to take into account that the demands of the new market segments of the country are related to academic innovation, and new teaching-learning processes and practices.